THE EFFECT OF PRODUCT QUALITY AND PRICE ON SHOPEE CONSUMER SATISFACTION IN BATAM CITY - Bella Rizki Putri; David Humala Sitorus (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of price and product quality on shopee e-commerce customer satisfaction. The population in this study are consumers who use Shopee e-commerce in Batam City. The sample taken is 100 residents of Batam city who have made a purchase at e-commerce shopee. The data collection method used is through the distribution of personal questionnaires. The analytical tool used in this research is multiple linear regression. The results obtained in this study have several findings, firstly, product quality has a positive and significant effect on customer satisfaction, secondly, the effect of price has a positive and significant effect on customer satisfaction, the third jointly product quality and price have a significant effect on customer satisfaction.